The impact of WRF vertical resolution on the simulated thermal-dynamic structures and intensity of Typhoon Lekima - Lian, Qinlai; Zhang, Yu; Liu, Xiaoyu; Xu, Jianjun (Frontiers in Earth Science, 2024)
This study utilizes the Weather Research and Forecasting (WRF) to comparatively analyze the impact of three vertical grid resolution (VGR) enhancement schemes on the simulation of super typhoon Lekima under two different horizontal resolutions. The relationship between structural changes and typhoon intensity is explored from the perspective of the simulated threedimensional thermodynamic and dynamic structure of the typhoon. The main conclusions obtained are as follows: Typhoon track simulation is not sensitive to the setting of VGR, while intensity simulation is greatly affected by it. Increasing VGR in the lower layer can enhance the simulated intensity of the typhoon, but when VGR enhancement is made in the middle layer, the simulated typhoon intensity decreases. For VGR enhancement in the upper levels, it is only when coupled with a simultaneous increase in horizontal resolution that the simulated typhoon intensity is enhanced. Different VGR enhancement schemes result in significant differences in the simulated thermodynamic and dynamic structures of the typhoon, which is a crucial factor causing variations in simulated typhoon intensity. In terms of dynamics, increasing VGR in the lower layer reduces the hydrostatic stability of the lower troposphere, which enhances convection and improves its symmetry. This leads to strengthened inflow and outflow activities of the typhoon, resulting in a stronger simulated typhoon with a tighter and straighter eyewall. In terms of thermal structure, increasing VGR in both the lower and upper levels enhances the warm core of the typhoon, thereby increasing its simulated intensity. However, the warm core simulated with upper layer enhancement extends to a higher altitude. This may be related to two different heating mechanisms, where lower layer VGR enhancement has a more pronounced effect on changes in boundary layer latent heat flux, while upper layer VGR enhancement promotes more sinking of high-entropy air from higher levels.